Characterizing healthy samples for studies of human cognitive aging - Geldmacher, David S.; Levin, Bonnie E.; Wright, Clinton B. (Frontiers in Aging Neuroscience, 2012)
Characterizing the cognitive declines associated with aging, and differentiating them from the effects of disease in older adults, are important goals for human neuroscience researchers. This is also an issue of public health urgency in countries with rapidly aging populations. Progress toward understanding cognitive aging is complicated by numerous factors. Researchers interested in cognitive changes in healthy older adults need to consider these complexities when they design and interpret studies. This paper addresses important factors in study design, patient demographics, co-morbid and incipient medical conditions, and assessment instruments that will allow researchers to optimize the characterization of healthy participants and produce meaningful and generalizable research outcomes from studies of cognitive aging. Application of knowledge from well-designed studies should be useful in clinical settings to facilitate the earliest possible recognition of disease and guide appropriate interventions to best meet the needs of the affected individual and public health priorities.